Food insecurity during the first year of the COVID-19 pandemic in four African countries. (August 2022) - Rudin-Rush, Lorin; Michler, Jeffrey D.; Josephson, Anna; Bloem, Jeffrey R.
Abstract: We document trends in food security up to one full year after the onset of the COVID-19 pandemic in four African countries. Using household-level data collected by the World Bank, we highlight differences over time amid the pandemic, between rural and urban areas, and between female-headed and male-headed households within Burkina Faso, Ethiopia, Malawi, and Nigeria. We first observe a sharp increase in food insecurity during the early months of the pandemic with a subsequent gradual decline. Next, we find that food insecurity has increased more in rural areas than in urban areas relative to pre-pandemic data within each of these countries. Finally, we do not find a systematic difference in changes in food insecurity between female-headed and male-headed households. These trends complement previous microeconomic analysis studying short-term changes in food security associated with the pandemic and existing macroeconomic projections. Highlights: We document trends in food security during the first year of the COVID-19 pandemic. We see a sharp increase in food insecurity during the early months of the pandemic. Food insecurity has increased more in rural areas than in urban areas. We find no differences in trends between female- and male-headed households.